SIGNIFIKANSI ASBAB AL-NUZUL DALAM PENAFSIRAN AL-QUR’AN - Selmiana Salam; Nasrullah Bin Sapa (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
Asbab al-nuzul (the reasons for the descent of verses) is an important element in understanding the historical context and the purpose of the descent of the verses of the Qur'an. Knowledge of asbab al-nuzul helps mufasir in interpreting verses more accurately, avoiding misinterpretations, and ensuring an understanding that is in harmony with the original intent of the revelation. This article explores the role and significance of asbab al-nuzul in the methodology of Qur'anic interpretation, emphasizing its relevance in dealing with contemporary issues. By understanding the background of the descent of verses, mufasir can explore deeper meanings, understand the legal context, and answer questions arising from social and cultural changes. The study also highlights how knowledge of asbab al-nuzul can support the development of a thematic and comprehensive interpretive approach. In conclusion, asbab al-nuzul is an important key in maintaining the integrity and relevance of the interpretation of the Qur'an in various eras.